Pengaruh Pertumbuhan Ekonomi, Pendapatan Asli Daerah dan Dana Alokasi Umum terhadap Belanja Modal - Triana Herawati; Iin Indarti (STIE Widya Manggala, 2014)
The purpose of this research was to know the influence of Economic Growth,Regional Own Revenue, and General Allocation Fund on Capital Expenditure partially and simultaneously from regency / city in West Java Province during period 2011-2012. The data used was secondary data from Central Bureau Statistics of West Java. Method of data collection was documentation. Multiple linier regression was used to analyze the data using SPSS version 16 before that, it was conducted classical assumption test to know a good model in statistics and then it conducted hypothesis test using t test and F test. Research results showed partially regional own revenue and general allocation fund significantly influenced capital expenditure and economic growth didn't influence capital expenditure.Simultaneously economic growth, regional own revenue, and general allocation fund influenced capital expenditure as high as 60,1 %.